Analysis of spontaneous, conversational speech in dementia of Alzheimer type: Evaluation of an objective technique for analysing lexical performance - Bucks, R; Singh, S; Cuerden, J; Wilcock, G (2000)
Spontaneous, conversational speech in probable dementia of Alzheimer type (DAT) participants and healthy older controls was analysed using eight linguistic measures. These were evaluated for their usefulness in discriminating between healthy and demented individuals. The measures were; noun rate, pronoun rate, verb rate, adjective rate, clause-like semantic unit rate (all per 100 words), including three lexical richness measures; type token ratio (TTR), Brunet's Index (W) and Honore's statistic (R). Results suggest that these measures offer a sensitive method of assessing spontaneous speech output in DAT. Comparison between DAT and healthy older participants demonstrates that these measures discriminate well between these groups. This method shows promise as a diagnostic and prognostic tool, and as a measure for use in clinical trials. Further validation in a large sample of patient versus control 'norms' in addition to evaluation in other types of dementia is considered.